2021
DOI: 10.1073/pnas.2100566118
|View full text |Cite
|
Sign up to set email alerts
|

Short-term high-fat feeding exacerbates degeneration in retinitis pigmentosa by promoting retinal oxidative stress and inflammation

Abstract: A high-fat diet (HFD) can induce hyperglycemia and metabolic syndromes that, in turn, can trigger visual impairment. To evaluate the acute effects of HFD feeding on retinal degeneration, we assessed retinal function and morphology, inflammatory state, oxidative stress, and gut microbiome in dystrophic retinal degeneration 10 (rd10) mice, a model of retinitis pigmentosa, fed an HFD for 2 to 3 wk. Short-term HFD feeding impaired retinal responsiveness and visual acuity and enhanced photoreceptor degeneration, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Recent study has demonstrated that gut microbiota dysbiosis could increase the laser-induced choroidal inflammation and neovascularization through inducing increased intestinal permeability and metabolic endotoxemia in HFD (7 weeks) feeding mice ( Andriessen et al., 2016 ). In retinitis pigmentosa (RP) model mice, short-term (2-3 weeks) HFD induced the retinal injury accompanying with the changes in gut microbiome ( Kutsyr et al., 2021 ). However, this association between retina and gut microbiota didn’t be found in HFD alone-induced C57BL/6J mice ( Kutsyr et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has demonstrated that gut microbiota dysbiosis could increase the laser-induced choroidal inflammation and neovascularization through inducing increased intestinal permeability and metabolic endotoxemia in HFD (7 weeks) feeding mice ( Andriessen et al., 2016 ). In retinitis pigmentosa (RP) model mice, short-term (2-3 weeks) HFD induced the retinal injury accompanying with the changes in gut microbiome ( Kutsyr et al., 2021 ). However, this association between retina and gut microbiota didn’t be found in HFD alone-induced C57BL/6J mice ( Kutsyr et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In retinitis pigmentosa (RP) model mice, short-term (2-3 weeks) HFD induced the retinal injury accompanying with the changes in gut microbiome ( Kutsyr et al., 2021 ). However, this association between retina and gut microbiota didn’t be found in HFD alone-induced C57BL/6J mice ( Kutsyr et al., 2021 ). In the current study, we investigated whether the cross-talks exits between gut and retina in long-term (5 months) HFD alone-induced C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%
“…Diet-induced microbial perturbations increase gut permeability, resulting in increased circulation of bacterial products such as lipopolysaccharides (LPS) and various pathogen-associated pattern molecules (PAMPs) [10,17 ▪ ,18 ▪ ,19 ▪ ]. This low-grade systemic inflammation potentially precipitates RPE inflammation and increases activated microglia infiltration through pattern recognition receptors, as supported by Andriessen et al [14] in animal studies [12,20 ▪ ,21]. HFD-induced gut dysbiosis was associated with elevated systemic and choroidal inflammatory mediators like IL-1β, IL-6, TNF-α, IL-17A, IFN-γ and vascular endothelial growth factor (VEGF) [12,20 ▪ ].…”
Section: Age-related Macular Degenerationmentioning
confidence: 95%
“…HFD consumption led to gut dysbiosis, characterized by the abundance of potentially pro-inflammatory bacteria, including Proteobacteria phylum (Bilophila sp. ), Bacteroidetes phylum (Alistipes sp) and Deferribacteraceae phylum (Mucispirillum schaedleri sp) [20 ▪ ]. These microbial changes were accompanied by augmented inflammatory and oxidative marker expression in the retinas, suggesting that the diet-gut microbiome axis can play a role in IRD pathogenesis [19 ▪ ,20 ▪ ].…”
Section: Inherited Retinal Dystrophiesmentioning
confidence: 99%
See 1 more Smart Citation